THE ROLE OF CONVERSATION CLUBS IN DEVELOPING ENGLISH SPEAKING FLUENCY - Maxmanazarova Feruza Ismoilovna; Eshmurzayeva Kamola (THE USE OF MODERN DIGITAL TECHNOLOGIES IN LINGUISTICS AND FOREIGN LANGUAGE TEACHING. INTERNATIONAL SCIENTIFIC AND PRACTICAL CONFERENCE, 2026)
This scientific article explores in depth the role of conversation clubs in enhancing English speaking fluency among language learners. The study focuses on communicative language teaching principles, the importance of interactive learning environments, and the psychological factors that influence speaking performance. The findings indicate that consistent participation in structured conversation clubs significantly improves learners’ fluency, pronunciation, vocabulary acquisition, and confidence in spoken English.